Metabolism and signaling crosstalk in glioblastoma progression and therapy resistance - Laura Zarzuela; Raúl V. Durán; Mercedes Tomé (Molecular Oncology)
Glioblastoma is the most common form of primary malignant brain tumor in adults and one of the most lethal human cancers, with high recurrence and therapy resistance. Glioblastoma cells display extensive genetic and cellular heterogeneity, which precludes a unique and common therapeutic approach. The standard of care in glioblastoma patients includes surgery followed by radiotherapy plus concomitant temozolomide. As in many other cancers, cell signaling is deeply affected due to mutations or alterations in the so‐called molecular drivers. Moreover, glioblastoma cells undergo metabolic adaptations to meet the new demands in terms of energy and building blocks, with an increasing amount of evidence connecting metabolic transformation and cell signaling deregulation in this type of aggressive brain tumor. In this review, we summarize some of the most common alterations both in cell signaling and metabolism in glioblastoma, presenting an integrative discussion about how they contribute to therapy resistance. Furthermore, this review aims at providing a comprehensive overview of the state‐of‐the‐art of therapeutic approaches and clinical trials exploiting signaling and metabolism in glioblastoma.